(untitled) (Interdisciplinary Studies Journal, 2024)
The support for students with indicators of high abilities/giftedness (HA/GT) in regular schools has been foreseen since Law No. 12,796/2013 in the special education modality; however, few practices are directed towards these students. In the context of regular schools, the curriculum of the New High School, established in 2017, stands out, consisting of a general basic education part and a diversified part that aims for students to take curricular units based on their interests. In this way, thinking about applying activities based on HA/GT for the diversified core is feasible, as the curriculum allocates hours for learning situations tailored to the students’ specificities. This study aims to investigate the applicability of a pedagogical resource based on the principles of HA/GT for activities in the diversified core in full-time high schools. It is a mixed research study with quantitative and qualitative strategies, bibliographical and documentary, using action research, which aims to improve practice. The results indicate the need for school professionals’ knowledge about HA/GT and that the proposed Guiding Guide is feasible, as it will promote stimulation, recognition, and appreciation of students’ interests, potentialities, and abilities.